2006
DOI: 10.1002/jcp.20662
|View full text |Cite
|
Sign up to set email alerts
|

Human fibroblasts undergo oxidative stress‐induced apoptosis without internucleosomal DNA fragmentation

Abstract: In order to evaluate the reliability of fibroblasts as a cell model for studying apoptosis, we tested the response of normal human fibroblasts to the oxidative stress inducers H(2)O(2) and 2-deoxy-D-ribose (dRib). Our results showed that fibroblasts treated with dRib and H(2)O(2) are induced to undergo apoptosis as demonstrated by reduction in total cell number, chromatin condensation, phosphatidylserine (PS) exposure, activation of caspase-3 and 7, changes in mitochondrial membrane potential and increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 57 publications
4
18
0
Order By: Relevance
“…In addition, it has been previously reported that H 2 O 2 stimulates BK channels through the NO/ sGC/cGMP pathway in cultured human endothelial cells and HEK293 cells that express BK channels (Dong et al, 2008;Ma et al, 2010). Therefore, these observations indicate that the same ion channel could be Although it has been accepted that apoptosis is characterised by distinct biochemical and morphological hallmarks, data from Formichi et al revealed that human dermal fibroblasts apoptosis induced by oxidising agents may occur in the absence of one of the characteristic features of apoptosis, namely internucleosomal DNA fragmentation (Formichi et al, 2006). In our experiment, we also did not observe H 2 O 2 -induced DNA fragmentation by agarose gel electrophoresis (data not show), the results are similar to those reported by Formichi et al These different cell behaviours may depend on the specific characteristics of human fibroblasts and may be related to the apoptotic stimulus used (Formichi et al, 2006).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, it has been previously reported that H 2 O 2 stimulates BK channels through the NO/ sGC/cGMP pathway in cultured human endothelial cells and HEK293 cells that express BK channels (Dong et al, 2008;Ma et al, 2010). Therefore, these observations indicate that the same ion channel could be Although it has been accepted that apoptosis is characterised by distinct biochemical and morphological hallmarks, data from Formichi et al revealed that human dermal fibroblasts apoptosis induced by oxidising agents may occur in the absence of one of the characteristic features of apoptosis, namely internucleosomal DNA fragmentation (Formichi et al, 2006). In our experiment, we also did not observe H 2 O 2 -induced DNA fragmentation by agarose gel electrophoresis (data not show), the results are similar to those reported by Formichi et al These different cell behaviours may depend on the specific characteristics of human fibroblasts and may be related to the apoptotic stimulus used (Formichi et al, 2006).…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, these observations indicate that the same ion channel could be Although it has been accepted that apoptosis is characterised by distinct biochemical and morphological hallmarks, data from Formichi et al revealed that human dermal fibroblasts apoptosis induced by oxidising agents may occur in the absence of one of the characteristic features of apoptosis, namely internucleosomal DNA fragmentation (Formichi et al, 2006). In our experiment, we also did not observe H 2 O 2 -induced DNA fragmentation by agarose gel electrophoresis (data not show), the results are similar to those reported by Formichi et al These different cell behaviours may depend on the specific characteristics of human fibroblasts and may be related to the apoptotic stimulus used (Formichi et al, 2006). In this study, we thus detected the effect of H 2 O 2 -enhanced K + current on cell injury in human dermal fibroblasts using a combination of PI and TUNEL assay staining, which indicated the cell death and apoptosis damage, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…Excessive apoptosis has been related to sepsis, ischemic heart disease, stroke, and neurodegenerative diseases, while functional deficiencies in the activation of apoptosis may facilitate the development of cancer and autoimmune diseases. 34 We examined the effects of disinfectants on cell death using an annexin V-FITC/PI assay at close to the LD 50 concentration (0.05, 0.1, and 0.5 mM). The dose-independent effect showed that H 2 O 2 , but not ClO 2 or NaOCl, induced cell death by producing an apoptotic signal at 0.05 and 0.1 mM (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The deregulation of apoptosis is implicated in a variety of diseases. Excessive apoptosis is related to sepsis, ischemic heart disease, stroke, and neurodegenerative diseases, and functional deficiencies in the activation of apoptosis may facilitate the development of certain cancers and autoimmune diseases 32) . During the early stages of apoptosis, a loss of phospholipid asymmetry occurs that results in the translocation of negatively charged phosphatidylserine (PS) from the inner to the outer leaflet of the cell membrane 33) .…”
Section: Discussionmentioning
confidence: 99%